THE EFFECT OF ENVIRONMENTAL SOCIAL AND GOVERNANCE (ESG) DISCLOSURE, LEVERAGE, AND ASSET MANAGEMENT EFFICIENCY ON PROFITABILITY (ANALYSIS OF ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2023-2024) - Nurul Aulia; Nor Norisanti; Resa Nurmala (RADJA PUBLIKA, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) disclosure, leverage, and asset management efficiency on the profitability of energy companies listed on the Indonesia Stock Exchange from 2023-2024. A quantitative approach was employed, using panel data analysis on a sample of 50 financial reports. The findings revealed that while ESG disclosure does not have a significant direct impact on Return on Equity (ROE), and leverage has a significant negative impact on the ROE, total asset turnover (TATO) does significantly and positively influence ROE. This suggests that asset management efficiency is the primary driver of profitability in the Indonesian energy sector, while ESG practices and leverage strategies require further development to demonstrate a tangible impact on financial performance.